2011
DOI: 10.1103/physreva.83.063608
|View full text |Cite
|
Sign up to set email alerts
|

Beyond mean-field dynamics in open Bose-Hubbard chains

Abstract: We investigate the effects of phase noise and particle loss on the dynamics of a Bose-Einstein condensate in an optical lattice. Starting from the many-body master equation, we discuss the applicability of generalized mean-field approximations in the presence of dissipation as well as methods to simulate quantum effects beyond mean-field by including higher-order correlation functions. It is shown that localized particle dissipation leads to surprising dynamics, as it can suppress decay and restore the coheren… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
173
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(179 citation statements)
references
References 47 publications
5
173
1
Order By: Relevance
“…It was also shown that the quantum coherence of a strongly interacting BEC loaded in the double-well trap subject to the phase noise and particle loss can be completely restored by engineering the parameters of the system and controlling the dissipation rate [17]. Similar results were obtained with the optical lattices, where the particle loss at the boundary acting together with the nonlinearity resulted in restoration of the coherence and formation of the discrete breathers [18]. Whereas in the previous setups the action of a localized or boundary dissipation was considered, in the present proposal we consider the action of a periodic dissipation which profoundly affects the physics in the optical lattice.…”
Section: Introductionsupporting
confidence: 69%
“…It was also shown that the quantum coherence of a strongly interacting BEC loaded in the double-well trap subject to the phase noise and particle loss can be completely restored by engineering the parameters of the system and controlling the dissipation rate [17]. Similar results were obtained with the optical lattices, where the particle loss at the boundary acting together with the nonlinearity resulted in restoration of the coherence and formation of the discrete breathers [18]. Whereas in the previous setups the action of a localized or boundary dissipation was considered, in the present proposal we consider the action of a periodic dissipation which profoundly affects the physics in the optical lattice.…”
Section: Introductionsupporting
confidence: 69%
“…In [16,17] it was shown that localized single particle losses can be used to create stable nonlinear structures. For instance, a discrete breather can emerge in a lattice with boundary losses or a coherent dark soliton can be engineered with the help of phase imprinting and localized losses.…”
Section: Discrete Breather Formationmentioning
confidence: 99%
“…In the presence of dissipation the dynamics is usually given by a master equation in Lindblad form [4,11,[13][14][15][16][17][18][19][20][21] …”
Section: Dissipative and Noisy Bose-hubbard Modelsmentioning
confidence: 99%
“…This not only exhibits rich phenomenology but can also provide a platform for future applications of quantum technologies. Dissipation induces decoherence [1][2][3][4], influences the correlations and dynamics [5][6][7][8][9][10][11][12][13][14][15][16][17], and engineering dissipative coupling may be employed in state preparation [18][19][20].…”
Section: Introductionmentioning
confidence: 99%